Re-Sedimentation Of The Sea Over A Sea Sand Export License And Its Implications For Marine Natural Resources: A Review Of Indonesian Positive Law - Saputra, Deo Renaldi; Hafida Aristya Arditha; Marisa Bahaj; Sarifah, Nurhidah; Sari, Intan Putri Ananda (Universitas Sains dan Teknologi Komputer, 2023)
Indonesia is an archipelago with a diversity of natural resources contained in it, the natural resources in Indonesia must of course be preserved and maintained by the Government of Indonesia through a rule, but the rules made by the Indonesian government still cause loopholes to environmental destruction, so this research will discuss two problems, namely the sea sand export permit can cause a marine environmental problem which ultimately causes disruption of marine resources and causes a sea re-sedimentation and the implementation of legal substance related to marine resources facing the threat of sea re-sedimentation due to sea sand exploration. The method used is a literature review with the result that the enforcement of the sea sand export policy can damage marine resources and intersect with the positive law of the marine environment